2015
DOI: 10.4236/ajac.2015.62013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Degradation Study of Lansoprazole, Identification, Isolation and Characterisation of Base Degradation Product

Abstract: Lansoprazole degradation is accelerated in both acidic and basic medium in water. The present investigation deals with the hydrolytic degradation of Lansoprazole. Acidic medium degradation show all known impurities and degradation products whereas basic degradation studies show new impurity which has higher molecular weight than Lansoprazole. New impurity was identified, isolated using mass based auto purification system and characterised by 1 H NMR, 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Earlier studies reported that lansoprazole was significantly more stable under basic and neutral hydrolyses than acidic hydrolysis or oxidation. Therefore, the forced degradation reactions were carried out at distinct incubation times with sampling performed at different time points; for more details refer to Table .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies reported that lansoprazole was significantly more stable under basic and neutral hydrolyses than acidic hydrolysis or oxidation. Therefore, the forced degradation reactions were carried out at distinct incubation times with sampling performed at different time points; for more details refer to Table .…”
Section: Resultsmentioning
confidence: 99%
“…6b. Battu and Pottabathini reported a new impurity, 7-(3-methyl-4-(2,2,2-trifluoroethoxy) pyridin-2-yl)-7H-benzo [4,5]imidazo [2,1b]benzo [4,5] imidazo [2,1-d]- [1,3,5]thiadiazine formed in harsh basic conditions [28] . DP-3(L), DP-4(A), DP-6(L) and DP-8(L), were formed in basic hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…LPZ was reported to degrade rapidly within 6-8 h in basic conditions, especially at high temperature (e.g. 60°C (Battu and Pottabathini, 2015) or 80°C (Shankar et al, 2017)). In this study, LPZ was incorporated in CD-MOFs at lower temperature (50°C) and during a 6 h procedure, in the presence of KOH (200 mM).…”
Section: Synthesis and Characterization Of Lpz Loaded Cd-mofsmentioning
confidence: 99%
“…1, upper panel). Moreover, LPZ is a fragile molecule which readily degrades in both acidic (DellaGreca et al, 2006;Ekpe and Jacobsen, 1999;Gupta et al, 2007) and basic conditions (Battu and Pottabathini, 2015;DellaGreca et al, 2006;Liu et al, 2005), even during storage at 4°C (DiGiacinto et al, 2000). It was interesting to study here whether the integrity of the drug was preserved upon incorporation in CD-MOFs and long-term storage.…”
Section: Introductionmentioning
confidence: 97%